MODERN METHODS IN THE TREATMENT OF DERMATOLOGICAL DISEASES (International journal of medical sciences, 2026)
Modern dermatology has undergone significant advancements in recent years, introducing innovative therapeutic approaches that target the underlying mechanisms of skin diseases. This review focuses on contemporary methods for the treatment of common dermatological conditions, including psoriasis, eczema, acne, vitiligo, and infectious dermatoses. Key interventions discussed include biological therapies, laser treatment, photodynamic therapy, minimally invasive aesthetic procedures, and personalized pharmacological strategies. The mechanisms of action, clinical effectiveness, safety profiles, and potential benefits of these methods are examined. Advanced diagnostic technologies, including dermoscopy, confocal microscopy, and AI-assisted imaging, are also highlighted for their role in enhancing treatment precision and individualized care. The review emphasizes the integration of these modern methods to improve clinical outcomes, patient satisfaction, and overall quality of life. Emerging trends such as gene therapy, stem cell applications, nanotechnology-based drug delivery, and digital health innovations are discussed as potential future directions. Overall, the application of modern dermatological methods represents a paradigm shift towards more effective, precise, and patient-centered care.